2016
DOI: 10.31018/jans.v8i2.839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of integrated nutrient management practices on dry matter production, yield and NPK uptake of transplanted rice (Oryza sativa)

Abstract: A field investigation was carried out during Rabi season (Pishanam rice) of 2012-2013 at wetland of Central Farm, Agricultural College and Research Institute, TNAU, Killikulam, to study the effect of integrated nutrient management practices on dry matter production, yield and NPK uptake of transplanted rice. The treatments were laid out in a Randomized Block Design and replicated thrice using the rice variety ADT(R) 45. Among the different integrated nutrient management practices, application of GLM @ 6.25 t h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
3
4
0
Order By: Relevance
“…Overall, the effect of seaweed extracts (liquid and granules) on rice (var.-Rajeshwari) nutrient uptake revealed that treatment-wise differences in the nutrient contents of rice grains and straws were found to be non-significant, while the fertility levels and the application of seaweed extracts had a significant impact on the nutrients that rice grains and straws absorbed. The similar results of this experiment were reported by Krishna Kumar et al, in 2005 [50] and Senthivelu et al, 2007 [51]. Table 4.…”
Section: Effect Of Seaweed Extract In Nutrient Uptake In Ricesupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the effect of seaweed extracts (liquid and granules) on rice (var.-Rajeshwari) nutrient uptake revealed that treatment-wise differences in the nutrient contents of rice grains and straws were found to be non-significant, while the fertility levels and the application of seaweed extracts had a significant impact on the nutrients that rice grains and straws absorbed. The similar results of this experiment were reported by Krishna Kumar et al, in 2005 [50] and Senthivelu et al, 2007 [51]. Table 4.…”
Section: Effect Of Seaweed Extract In Nutrient Uptake In Ricesupporting
confidence: 91%
“…1. Diagrammatic representation of the physiological reactions in plants induced bytreatments with seaweed extract[27]…”
mentioning
confidence: 99%
“…Dry matter production Results pertaining to both the consecutive years and pooled mean values (Table 1) revealed that irrespective of different treatments, dry matter yield of paddy increased with advancement of crop growth upto 90 DAT. The results were supported by Singh and Mandal (1997) [22] ; Shah and Kumar (2014) [19] and Jeyajothi and Durairaj (2016) [11] . In general comparatively higher dry matter yield of paddy was observed in soils amended with inorganic or organic sources of nitrogen applied either singly or in combination over control at different growth stages (Bar et al, 2004;Shah and Kumar, 2014 and Sahu et al, 2015) [4,19,17] .…”
Section: Resultssupporting
confidence: 60%
“…However, on 90 DAT, these treatments remained at par again with 75% RDN from urea + 25% RDN from FYM (T 5 ) and 50% RDN from urea + 50% RDN from FYM (T 6 ) amended soil followed by soil treated with 50% RDN from urea + 50% RDN from FYM + 10 tonnes Azolla ha -1 (T 11 ) showing similarity effects with the remaining N treatments except soil incorporated with 20 tonnes Azolla ha -1 (T 4 ) . Higher dry matter production might be due to increased availability of major nutrients through chemical fertilizer and mineralized nutrient from organic sources throughout the cropping period (Jeyajothi and Durairaj, 2016) [11] . This leads to enhancement of proficient growth and development of rice through highest uptake and utilization of the nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Lin and Lin (1985) reported that high N levels resulted in higher tiller number and leaf area index throughout the growing season of rice. Jeyajothi and Durairaj (2016) found that application of green leaf manure @ 6.25 t ha -1 + Azophosmet + 100% NPK registerd significantly the highest dry matter production at all growth stages of rice. The highest panicle length, number of spikelets panicle -1 and number of grains panicle -1 was recorded under treatment T 3 followed by treatment T 2 .…”
Section: Fig 1 Effect Of Nutrient Management Modules On N Uptake By Hybrid Rice Cropmentioning
confidence: 89%